Multiphoton fluorescence lifetime imaging microscopy (FLIM) and super-resolution fluorescence imaging with a supramolecular biopolymer for the controlled tagging of polysaccharides. Issue 19 (2nd May 2019) - Ge, Haobo; Cortezon-Tamarit, Fernando; Wang, Hui-Chen; Sedgwick, Adam C.; Arrowsmith, Rory L.; Mirabello, Vincenzo; Botchway, Stanley W.; James, Tony D.; Pascu, Sofia I.
Abstract : A new coumarin-appended boronate ester for fluorogenic imaging which binds polysaccharides in solution and in cells. Abstract : A new supramolecular polysaccharide complex, comprising a functionalised coumarin tag featuring a boronic acid and β-d -glucan (a natural product extract from barley, Hordeum Vulgare ) was assembled based on the ability of the boronate motif to specifically recognise and bind to 1, 2- or 1, 3-diols in water. The complexation ratio of the fluorophore : biopolymer strand was determined from fluorescence titration experiments in aqueous environments and binding isotherms best described this interaction using a 2 : 1 model with estimated association constants of K 2:1a1 = 5.0 × 10 4 M −1 and K 2:1a2 = 3.3 × 10 11 M −1 . The resulting hybrid (denoted5 @β-d -glucan) was evaluated for its cellular uptake as an intact functional biopolymer and its distribution compared to that of the pinacol-protected coumarin boronic acid derivative using two-photon fluorescence lifetime imaging microscopy (FLIM) in living cells. The new fluorescent β-d -glucan conjugate has a high kinetic stability in aqueous environments with respect to the formation of the free boronic acid derivative compound5 and retains fluorescence emissive properties both in solution and in living cells, as shown by two-photon fluorescence spectroscopy coupled with time-correlated single photon counting (TCSPC). Super-resolution fluorescence imaging using Airyscan detection as well as TM AFM and Raman spectroscopy investigations confirmed the formation of fluorescent and nano-dimensional aggregates of up to 20 nm dimensions which self-assemble on several different inert surfaces, such as borosilicate glass and mica surfaces, and these aggregates can also be observed within living cells with optical imaging techniques. The cytoplasmic distribution of the5 @β-d -glucan complex was demonstrated in several different cancer cell lines (HeLa and PC-3) as well as in healthy cells (J774.2 macrophages and FEK-4). Both new compounds (pinacol protected boronated coumarin)5-P and its complex hybrid5 @β-d -glucan successfully penetrate cellular membranes with the minimum morphological alterations to cells and distribute evenly in the cytoplasm. The glucan biopolymer retains its activity towards macrophages in the presence of the coumarin tag functionality, demonstrating the potential of this natural β-d -glucan to act as a functional self-assembled theranostic scaffold capable of mediating the delivery of anchored small organic molecules with imaging and drug delivery applications.